PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK UNTUK KETERAMPILAN BERBICARA: Development, Media, Speaking Skills - Zohana Hanif Saputri; Bayu Firmansyah (Institute Agama Islam Al-Qolam Malang, 2023)
This research started from the lack of variety of learning media in teaching and learning activities so it is necessary to develop a product in the form of comics as a learning medium. In the KD legend material. 311 and 4.11. The formulation of the problems contained in this study are: (1) How is the process of developing comic media for legend text speaking skills in seventh grade students of MTs Abu Amr. (This study aims to determine the process of developing comics media for legend text speaking skills in seventh grade students of MTs Abu Amr and the effectiveness of developing comic media for legend text speaking skills in seventh grade students of MTs Abu Amr. The research method used is Research and Development with the ADDIE model which includes 5 steps, namely analysis, design, development, implementation, evaluation. The results of the validation of 4 experts, namely 1 material expert, got an average score of 90% in the